THE VALUES OF RELIGIOUS MODERATION IN JAVANESE TRADITIONS (SATU SURO TRADITION OF JAVANESE PEOPLE) - Fadhila amalia, Fadhila Amalia (Fakultas Adab dan Humaniora UIN Sunan Gunung Djati Bandung, 2024)
This study aims to describe 'The Values of Religious Moderation in Javanese Tradition(One Suro Tradition of Javanese Society)'. Tradition is an activity or habit carried out fromgeneration to generation by local people from the past to the present. Each regional communityhas different traditions because each regional community has differences in its own customs,cultures, and beliefs. On the 1st of Muharram in Hijri i.e. on the Islamic calendar, the beginningof the month is correct In the Islamic New Year. Usually, Javanese people call it 'Satu Suro'.This research uses a descriptive qualitative method, namely by means of literature that willanalyze and compile information from certain sources about 'The Values of ReligiousModeration in the Javanese Community Tradition (One Suro Tradition of Javanese Society)'.In the results of this study, the tradition of one suro carried out by the Javanese community hasmany activities that are in accordance with the beliefs of each regional community. TheJavanese Muslim community performs prayers and reads year-end and early-year prayers towelcome the Islamic New Year, which is the month of Muharram, one of the great months.There are many values of religious moderation in the tradition of one suro practiced by theJavanese people.